When reality breaks from us: lived experience wisdom in the Covid-19 era. Issue 4 (1st October 2020) - Florence, Ana Carolina; Miller, Rebecca; Bellamy, Chyrell; Bernard, Pauline; Bien, Claire; Atterbury, Kendall; Bragg, Cheri; Diaz, Annette; Gardien, Eve; Guy, Kimberly; Hansen, Chris; Maclean, Kirsten; et al.
ABSTRACT: The emergence of Covid-19 disrupted most aspects of life, creating a high degree of uncertainty and unpredictability about the future. Knowledge from a place of lived experience offers insights and strategies to better understand how to live, grow and thrive through the difficulties that people who experience mental health challenges, other disabling health conditions, people of color, and people from lower socio-economic backgrounds have overcome. We report on a programmatic effort to investigate how lessons learned through lived experience could be useful to persons who are dealing with a destabilizing situation like this pandemic for the first time, especially mental health providers. Three listening sessions over Zoom were conducted to gather information, views and personal accounts related to the current pandemic. Twenty four people with experience of mental health challenges and people living with disabilities, of various ethnic and racial backgrounds, participated in the sessions. We suggest that the recovery framework can be helpful to address the current crisis; we challenge traditional notions of normality; and finally, we recommend that providers and systems of care adopt a framework that addresses health inequities and human rights.